A Nanosensor Platform for Biologging in Marine Animals - Rory Wilson (ACS Sensors)
Biologging has significantly advanced ecological biology by enabling the collection of data from free-roaming ani-mals in their natural habitats. Traditionally, these measurements have largely been limited to temperature, pressure, and movement. Incorporating physiological data of animal biomarkers could yield valuable orthogonal datasets, provid-ing a more nuanced understanding of organisms in the context of their environments and behaviors. Despite this poten-tial, successful collection of such biochemical information remains absent, and thus motivates new sensor platforms. To-wards this end, we explore the hardware and nanosensor optimization of animal implantable sensors for tracking hor-mone levels in marine animals. The transducer element is based on polymer-wrapped single-walled carbon nanotubes (SWCNT) that act as nanosensors embedded within a biocompatible poly (ethylene glycol) diacrylate (PEGDA) hydrogel. This work investigates the performance of the nanosensor hydrogel under various temperatures, illumination conditions, and nanoparticle concentration in the hydrogel. We further prototype a miniaturized fluores-cent system for integration into existing, commercially available acoustic tags widely used in marine biology studies. We demonstrate a baseline of 100 nM for the detection limit of progesterone as an example of an important hormone in marine animals, using the inte-grated nanosensor hydrogel in this platform. Further improvement is possible with optimization of the signal to noise via hardware development. This developed form-factor will complement the presently collected data by providing insights into the physiological state of the animals in the context of their behavior and environments.